1961
DOI: 10.1017/s0007485300055644
|View full text |Cite
|
Sign up to set email alerts
|

Field experiments on the control of wheat bulb fly, Leptohylemyia coarctata (Fall.)

Abstract: Although damage by wheat bulb fly, Leptohylemyia coarctata (Fall.), can be prevented or reduced by various cultural measures these are not always practicable (Gough, 1957) and chemical methods were therefore investigated. Preliminary experiments suggested that seed dressings would be the simplest and most promising approach as Gough & Cohen (1954) found that spraying to kill adults was unsatisfactory.Seed dressings containing 20 per cent, -y BHC to prevent wireworm damage were introduced commercially about 194… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1963
1963
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Dieldrin and y-BHC seed-dressings have been used for more than 10 years to control wheat bulb fly. Results of many trials have shown that y-BHC acts mainly by preventing larvae entering the plants and kills few larvae that succeed in entering, whereas dieldrin acts mainly by killing larvae after they enter (Gough & Woods, 1954;Bardner, 1958;Way, 1959;Maskell & Gair, 1961 ;Gough, Woods, Maskell & Towler, 1961). Both materials are less effective in organic soils than in mineral soils (Gough et al, 1961.…”
Section: Introductionmentioning
confidence: 99%
“…Dieldrin and y-BHC seed-dressings have been used for more than 10 years to control wheat bulb fly. Results of many trials have shown that y-BHC acts mainly by preventing larvae entering the plants and kills few larvae that succeed in entering, whereas dieldrin acts mainly by killing larvae after they enter (Gough & Woods, 1954;Bardner, 1958;Way, 1959;Maskell & Gair, 1961 ;Gough, Woods, Maskell & Towler, 1961). Both materials are less effective in organic soils than in mineral soils (Gough et al, 1961.…”
Section: Introductionmentioning
confidence: 99%
“…This contrast in accuracy could be related to specific environmental factors that limited shoot production such as soil capping or water logging (Robertson et al, 2009). Our revised thresholds for D. coarctata in winter wheat demonstrate that the current D. coarctata pest threshold of 250 eggs m -2 (Gough et al, 1961) is too simplistic and for many crops this likely represents either an overestimation of the potential pest damage, an underestimation of the amount of damage that can be tolerated by a winter wheat crop, or a combination of both factors. Sensitivity analysis (achieved by adjusting each parameter used in Equation 2 from its likely minimum value to its maximum value; Fig.…”
Section: Discussionmentioning
confidence: 90%
“…Crop tolerance, or the economic injury level, can be broadly defined as the amount of pest damage that a crop can withstand before an economic consequence is observed (Stern et al, 1959). The most recent D. coarctata pest thresholds of 250 or 100 eggs m -2 , for crops sown before the end of October and from November, respectively, were devised c. 60 years ago by Gough et al (1961) and only take account of pest abundance with no consideration of crop tolerance. Adjusting various agronomic factors, such as sowing date and seed rate, has been used to successfully achieve tolerance against other stem-boring pests of wheat, including the gout fly, Chlorops pumilionis (Bjerkander) (Bryson et al, 2005) and wheat saw fly, Cephus cinctus Norton (Beres et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Following the work of Gough (1946, 1947) on wheat bulb fly infestations in Yorkshire and the widespread and severe outbreaks of wheat bulb fly damage in the eastern counties in 1952 and 1953, entomologists in the National Agricultural Advisory Service, at Rothamsted and elsewhere, started much work on the biology, ecology and chemical control of wheat bulb fly. This work included such studies as those on diapause in the egg (Way, 1959a(Way, , 1960, effects of soil conditions on oviposition (Raw, 1955), estimation of crop losses (Raw & Lofty, 1957), host plant location (Stokes, 1956; Long, 1958), alternative hosts (Stokes, 1955), adult behaviour (Dobson, Stephenson & Lofty, 1958;Long, 1959;Dobson & Morris, 1960), parasites and predators, (Dobson, 1961), laboratory rearing (Bardner & Kenten, I957), and methods of controlling the pest with chemicals (Bardner 1958; Way, 1959b;Gough et al, 1961).…”
Section: I57 P a S T Work I N B R I T A I Nmentioning
confidence: 99%